Transcriptional and Posttranscriptional Regulations of the HLA-G Gene - Erick C. Castelli; Luciana C. Veiga-Castelli; Layale Yaghi; Philippe Moreau; Eduardo A. Donadi (Journal of Immunology Research)
HLA-G has a relevant role in immune response regulation. The overall structure of the HLA-G coding region has been maintained during the evolution process, in which most of its variable sites are synonymous mutations or coincide with introns, preserving major functional HLA-G properties. The HLA-G promoter region is different from the classical class I promoters, mainly because (i) it lacks regulatory responsive elements for IFN-γ and NF-κB, (ii) the proximal promoter region (within 200 bases from the first translated ATG) does not mediate transactivation by the principal HLA class I transactivation mechanisms, and (iii) the presence of identified alternative regulatory elements (heat shock, progesterone and hypoxia-responsive elements) and unidentified responsive elements for IL-10, glucocorticoids, and other transcription factors is evident. At least three variable sites in the 3′ untranslated region have been studied that may influence HLA-G expression by modifying mRNA stability or microRNA binding sites, including the 14-base pair insertion/deletion, +3142C/G and +3187A/G polymorphisms. Other polymorphic sites have been described, but there are no functional studies on them. The HLA-G coding region polymorphisms might influence isoform production and at least two null alleles with premature stop codons have been described. We reviewed the structure of the HLA-G promoter region and its implication in transcriptional gene control, the structure of the HLA-G 3′UTR and the major actors of the posttranscriptional gene control, and, finally, the presence of regulatory elements in the coding region.